Lysostaphin Treatment of Experimental Aortic Valve Endocarditis Caused by a Staphylococcus aureus Isolate with Reduced Susceptibility to Vancomycin - Patron, Roberto L. (American Society for Microbiology, 1999)
The rabbit model of endocarditis was used to test the effectiveness of vancomycin and two different lysostaphin dosing regimens for the treatment of infections caused by a Staphylococcus aureus strain with reduced susceptibility to vancomycin (glycopeptide-intermediate susceptible S. aureus [GISA]). Vancomycin was ineffective, with no evidence of sterilization of aortic valve vegetations. However, rates of sterilization of aortic valve vegetations were significantly better for animals treated with either a single dose of lysostaphin (43%) or lysostaphin given twice daily for 3 days (83%) than for animals treated with vancomycin. Rabbits given a single dose of lysostaphin followed by a 3-day drug-free period had mean reductions in aortic valve vegetation bacterial counts of 7.27 and 6.63 log(10) CFU/g compared with those for untreated control rabbits and the vancomycin-treated group, respectively. We conclude that lysostaphin is an effective alternative for the treatment of experimental aortic valve endocarditis caused by a clinical VISA strain.